Evaluation of Some Skill Tests in Football According to Construct Validity and Performance Analysis - Noori, Ali Sabah; Ashour , Aya Hashim; Jabir, Ali Basu; Abdul-Hussein , Abbas Zaki (مجلة دراسات وبحوث التربية الرياضية, 2025)
The study revealed challenges in accurately measuring students’ performance due to the limitations of certain tests in achieving the intended objectives. A descriptive approach was adopted to study the suitability of the tests used. The study sample consisted of 84 first-year students from the College of Physical Education and Sports Science at the University of Basra, representing 39% of the targeted population. Tools such as personal interviews, content analysis, and standard tests were employed to gather and analyse the data. The key findings indicated statistically significant differences between surface-level assessments and performance evaluations, particularly in aspects related to accuracy and timing. This underscores the need to develop evaluation methodologies for more accurate and objective measurements. The study’s main recommendation is to redesign skill tests to better align with educational and training objectives, taking into account the importance of accuracy and the timing of evaluations.